Pollution and National Accounting - John M. Hartwick (Queen's University, Department of Economics, 1990)
The current value Hamiltonian in an aggregate optimal growth problem with heterogeneous capital stocks including exhaustible, renewable and environmental stocks is the NNP function. Routine substitutions reveal that the using up of environmental capital (more pollution) is representable as an easy-to-interpret economic depreciation magnitude. We obtain a result which indicates when it is valid to net pollution abatement expenditures from GNP. We also obtain the general result: deduct rents on environmental capital reductions from GNP to get NNP.
Keywords: 330